Florística, solos e abundância isotópica de 13C em áreas de floresta e de campo no bioma Pampa - Andriollo, Daiane Deckmann (2015)
To establish strategies for use, management and conservation of the Pampa Biome, this research describes the current vegetation, soil physical properties and, to identified groups of plants that influenced on soil organic matter formation, natural abundance of δ13C. Areas containing forest and native grassland were used in farms belonging to CMPC Celulose Riograndense, located in São Gabriel, Rio Grande do Sul. We defined 35 samples units in grassland (17 units in Batovi Farm and 18 in Santa Olga Farm). In the forest area 60 sample units were made (40 units in Medium Forest Santa Olga and 20 sampling units in Initial Forest Santa Olga). In each horizon, soil bulk density, total porosity, macro and micro porosity, saturated hydraulic conductivity and particle size distribution were determined. For δ13C analyses different tissues of several plant species with the most frequent occurrence at sites with soil profiles in each area. For soil organic carbon and natural abundance of δ13C in the soil profile quantification, samples were obtained from depths of 0-5, 5-10, 10-20, 20-40, 40-60 and up to 140 cm. The survey and soil classification showed wide variation, with the following main classes: Ultisol, Entisol, and Vertisol (Soil Taxonomy, USDA). The most representative botanic families found in grassland with were Poaceae, Asteraceae, Apiaceae and Fabaceae, while in forest were Myrtaceae and Euphorbiaceae. Regarding the abuncance of δ13C in plant, grassland species fall within C4 and forest in C3 plant. Soil organic carbon content was higher in forest areas than in grassland. For Batovi grassland soil natural abundance of δ13C is in C4 plants interval, Santa Olga grassland followed the same trend until the first 100 cm depth, and afterwads, natural abundance of δ13C is in the middle range, in which there may have occurred influence of C3 and C4 plants. The abundance of δ13C change of soil in Medium Forest Santa Olga was perceptible below 20 cm depth, while in Initial Forest Santa Olga below 10 cm, which suggest a change of predominant vegetation in the past.